Fingers hold spatial information that toes do not. Issue 1 (January 2021) - Manser-Smith, Kelda; Romano, Daniele; Tamè, Luigi; Longo, Matthew R.
Fingers have preferential associations with relative spatial locations. Tactile localisation is faster when the fingers are in these locations, such as when the index finger is in a relatively higher spatial position, and the thumb in a relatively lower position. However, it is unclear whether these associations are related to hands specifically, or are a more general characteristic of limbs. The present study therefore investigated whether toes have similar spatial associations. If these associations reflect the statistics of natural limb usage, very different patterns of association would be expected for the fingers and toes, given their different functional roles in daily behaviour. We measured reaction time (RT) and error rates of responses to tactile stimuli applied to the middle finger/toe or thumb/big toe, when they were positioned in a relative upper or lower location. We replicated the finding that fingers have preferential associations that facilitates localisation—RT and error rate were lower when the index finger was in the top position, and the thumb in the bottom position. We found that toes do not hold the same spatial information, though it remains unclear whether toes hold different spatial information or none at all. These results demonstrate spatial information held by the fingers is stronger and more reliable than for the toes, so is not a general characteristic of limbs, but possibly related to hand use.